2022
DOI: 10.3168/jds.2021-21125
|View full text |Cite
|
Sign up to set email alerts
|

Genomic inbreeding coefficients using imputed genotypes: Assessing different estimators in Holstein-Friesian dairy cows

Abstract: The objective of this study was to estimate inbreeding coefficients in Holstein dairy cattle using imputed SNPs data. A data set of 95,540 Italian Holstein dairy cows from the routine genomic evaluations of the Italian National Association of Holstein, Brown, and Jersey Breeders were analyzed, with 84,445 imputed SNP. Ten widely used genomic inbreeding estimators were tested, including 4 PLINK v1.9 estimators (F, F HAT1 , F HAT2 , F HAT3 ), 3 genomic relationship matrix (GRM)-based methods [VanRaden's first me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 79 publications
2
22
3
Order By: Relevance
“…The latter (called in the software PLINK and GCTA) is almost never used in practice. However, ( in PLINK and GCTA) has been considered on many occasions [ 12 , 41 , 43 , 44 , 50 , 58 ]. Our results argue against the use of both these estimators, as they showed the lowest correlations with and the most biased estimates of ΔID in the majority of scenarios, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter (called in the software PLINK and GCTA) is almost never used in practice. However, ( in PLINK and GCTA) has been considered on many occasions [ 12 , 41 , 43 , 44 , 50 , 58 ]. Our results argue against the use of both these estimators, as they showed the lowest correlations with and the most biased estimates of ΔID in the majority of scenarios, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used a terminology, as simple as possible, by identifying the abbreviation for the authors who originally proposed the estimators ( VR , YA , LH ) plus a suffix 1 to indicate that the measure is obtained from a ratio of averages over loci ( VR 1, YA 1, LH 1) and a suffix 2 when the same estimator is obtained from the average of the ratios ( VR 2, YA 2, LH 2). This may simplify the existing “Babel tower” [ 44 ] of nomenclature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FPED_FULL and FPED found can be considered to be low when compared to inbreeding coefficients reported in previous studies in Guzerá breed (Pereira et al, 2016), in indicine Gyr cattle (Santana et al, 2014;Peripolli et al, 2018) and taurine breeds (Zhang et al, 2015;Dadousis et al, 2022). An interesting result emerged when comparing our results with the study of .…”
Section: Discussioncontrasting
confidence: 63%
“…FROH values were lower than those reported for Gyr cattle (Peripolli et al, 2018;Mulim et al, 2022) and higher than those reported for Nellore cattle (Mulim et al, 2022) and taurine breeds (Zhang et al, 2015;Dadousis et al, 2022). However, these values may vary even within the same breed (Peripolli et al, 2018;Mulim et al, 2022), as they depend on the number of animals genotyped, the density of markers, and the parameters used to determine ROHs.…”
Section: Discussioncontrasting
confidence: 55%